2016
DOI: 10.1371/journal.pone.0159092
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Proliferation and Migration by miR-203 via GAS41/miR-10b Axis in Human Glioblastoma Cells

Abstract: Glioma amplified sequence 41(GAS41) is a potent transcription factor that play a crucial role in cell proliferation and survival. In glioblastoma, the expression of GAS41 at both transcriptional and post transcriptional level needs to be tightly maintained in response to cellular signals. Micro RNAs (miRNA) are small non coding RNA that act as important regulators for modulating the expression of various target genes. Studies have shown that several miRNAs play role in the post-transcriptional regulation of GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
0
12
0
1
Order By: Relevance
“…Decreased miR-203a levels may yield an imbalance in proliferation and differentiation that may yield uncontrolled proliferation and tumor formation. This may explain why expression of miR-203a is diminished in bladder cancer, prostate cancer, esophageal squamous cell carcinoma, and human glioblastoma 14 - 17 . We demonstrated in the current study that the expression of miR-203a is significantly lower in cholesteatoma than in normal retroauricular skin (Figure 1 A,B,C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased miR-203a levels may yield an imbalance in proliferation and differentiation that may yield uncontrolled proliferation and tumor formation. This may explain why expression of miR-203a is diminished in bladder cancer, prostate cancer, esophageal squamous cell carcinoma, and human glioblastoma 14 - 17 . We demonstrated in the current study that the expression of miR-203a is significantly lower in cholesteatoma than in normal retroauricular skin (Figure 1 A,B,C).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators previously have demonstrated that miR-203a is specific to epithelial tissue; affects the growth, differentiation, and function of keratinocytes; and is an important contributor to skin development 11 - 13 . In many tumors, miR-203a has been shown to prevent or suppress cancer 14 - 17 . Like the skin, a cholesteatoma is composed primarily of keratinocytes; like a tumor, the keratinocytes of a cholesteatoma exhibit abnormal proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotide has-miR-203 mimics (miR-203) were designed as described previously [19], and a non-specific sequence was used as a negative control (miR-NC). The miR-203 plasmid construct was chemically synthesized by Gene Pharma (Shanghai, China) and is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Its mechanism of action to regulate tumor cell invasion and metastasis has become a focus in the research field. 18,19 And a large number of studies confirmed that tumor invasion and metastasis are related to miRNA. 20,21 Yanaihara et al 22,23 found that miR-125a was located in 19q13.41 and analyzed the lung cancer tissues and the corresponding adjacent lung tissues with core chip, which displayed that expression of miR-125a in lung cancer tissues was lower than that in the adjacent lung tissues.…”
mentioning
confidence: 99%